Konsep Radha’ah: Jumlah Persusuan Yang Menjadikan Mahram Menurut Para Ulama - Aina, Nadhrah; Rusdiyah, Rusdiyah; Sa'adah, Sa'adah (Sharia Journal and Education Center Publishing, 2023)
Abstract This paper explores the concept of Radha'ah, a practice of breastfeeding recognized by Islamic scholars. Radha'ah refers to the act of nursing that establishes a mahram relationship between the nursing mother and the nursed individual. The discussion involves the perspectives and assessments of prominent Islamic scholars regarding the legitimacy and relevance of this concept within the framework of Sharia. The research delves into the legal foundations and hadiths that discuss Radha'ah, exploring the scholars' understanding and interpretations that either support or oppose it. Analysis of this concept involves an understanding of the conditions that must be met for a mahram relationship to be established through the practice of Radha'ah. The study also highlights the historical and cultural contexts shaping scholars' perceptions of this practice. Furthermore, this paper investigates the practical implications of Radha'ah in the everyday lives of Muslims. In discussing this aspect, attention is given to how the understanding of Radha'ah contributes to a broader comprehension of Islamic family dynamics and societal norms. Keywords: Radha’ah, hadits, Mahram ABSTRAK Mengulas konsep Radha'ah, sebuah praktek persusuan yang mendapatkan pengakuan dari para ulama Islam. Radha'ah merujuk pada tindakan menyusui yang dapat menjadikan dua individu yang terlibat sebagai mahram. Diskusi melibatkan pandangan dan penilaian para ulama terkemuka dalam Islam terhadap keabsahan dan relevansi konsep ini dalam konteks syariah. Penelitian ini mendalam ke dalam landasan hukum dan hadis yang membahas Radha'ah, mengeksplorasi pemahaman dan interpretasi ulama yang memperkuat atau menentangnya. Analisis terhadap konsep ini melibatkan pemahaman tentang syarat-syarat yang harus dipenuhi agar hubungan mahram dapat terbentuk melalui praktik Radha'ah. Penelitian ini juga menyoroti konteks historis dan budaya yang membentuk pemahaman para ulama terkait dengan praktik ini. Selain itu, makalah ini menggali implikasi praktis Radha'ah dalam kehidupan sehari-hari umat Islam. Dalam membahas hal ini, diperhatikan bagaimana pemahaman terhadap Radha'ah dapat memberikan kontribusi dalam pemahaman keluarga dan masyarakat Islam secara lebih luas. Kata Kunci : Radha’ah, hadis, Mahram